Familial hemophagocytic lymphohistiocytosis in two brothers - Gan, Gin Gin; Eow, Geok Im; Teh, A.; Ng, S.C.; Sangkar, J.V. (Malaysian Medical Association, 2004)
Familial hemophagocytic lymphohistiocytosis is a disorder which presents with fever, pancytopenia, liver dysfunction and also an increase in non-malignant histiocytes with prominent hemophagocytosis in various organs. It is usually difficult to distinguish from other hemophagocytic syndrome in the absence of family history. It rarely manifests in adults. Chemotherapy is usually indicated. Here, we report the occurrence of this disorder in two brothers in their twenties.